Utility of tryptase genotyping in the screening, diagnosis, and management of systemic mastocytosis - McMurray, Jeremy C.; Schornack, Brandon J.; Villar, Joaquin; George, Tracy I.; Boggs, Nathan A. (Frontiers in Allergy, 2025)
Tryptase genotyping has an expanding role in the screening, diagnosis, and management of patients with systemic mastocytosis (SM). Reference ranges for basal serum tryptase (BST) based on increased TPSAB1 gene copy number can guide whether a patient's BST value is normal according to their specific tryptase genotype. Patients with an elevated BST based upon their tryptase genotype should be offered a bone marrow biopsy with sample evaluation by a hematopathologist. Tryptase genotyping is required when assessing patients for the WHO minor criterion, BST > 20 ng/ml, especially in those with monoclonal mast cell activation syndrome, bone marrow mastocytosis (BMM), and indolent systemic mastocytosis (ISM) when the major criterion is not met. Additionally, in patients with non-advanced SM, tryptase genotyping helps determine whether a patient with hereditary-alpha tryptasemia (HαT) has BMM with a BST < 125 ng/ml or fulfills the B-finding of BST > 200 ng/ml through application of a correction factor. Understanding a patient's BST level based upon their tryptase genotype also is helpful in guiding when to pursue a repeat bone marrow biopsy in patients with SM treated with a tyrosine kinase inhibitor (TKI). However, TKIs have variable KIT D816V as well as wild type KIT inhibition. Given this variable KIT inhibition, ongoing and future clinical trials with selective TKIs should report whether patients with SM and HαT experience normalization or persistent elevation of BST values as this is essential in understanding the expected treatment response and when to assess for pathological remission in the bone marrow.